Solutions to enhance primary school teachers' Awareness of the Role of STEM in primary school - Tiep, Pham Quang (Technium Social Sciences Journal, 2023)
STEM education in primary school is designed to provide a foundation for future learning in these subjects, as well as to develop critical thinking and problem-solving skills, which are important for success in many areas of life. By engaging students in hands-on, practical learning experiences, STEM education can help prepare them for the challenges and opportunities of the future. Primary school is an ideal time to introduce STEM concepts and practices to students. Children in primary school are naturally curious about the world around them, and STEM education can help them develop the skills and knowledge needed to systematically and structurally explore that world.